Diversity in floral characters of monoecious nutmeg (Myristica fragrans Houtt.) - K V Saji, M Anandaraj, S Aarthi, J Rema, B Sasikumar, (Journal of Spices and Aromatic Crops, 2018)
Floral diversity in monoecious type nutmeg reveals three types of flowers namely; pistillate, staminate and hermaphrodite flowers. The structure of hermaphrodite flowers in nutmeg is reported for the first time. The flowers are borne on the leaf axil, flowering habit of the three types of flowers are seen in cymes as well solitary in the same tree. The gynoecium consists of single ovary with bifid stigma in the pistillate flowers and the androecium of staminate flowers has adnate 7-13 anthers. Intra flower variability is evident in case of hermaphrodite flowers. In hermaphrodite flower the androecium ranges with 1-4 anthers, in the form of fused filament or free filament or both; some anthers are fused with the gynoecium. Besides remnants of the stamen in the developed fruits of hermaphrodite flowers, staminodes are also observed in the flowers. Colour of all the three types of flowers are light creamy yellow, with thick gamosepalous perianth which bursts as bilobed, trilobed, tetralobed and pentalobed lobes during anthesis. Analysis of variance of trees for flower types and floral attributes like flower type, number of anthers, length of anthers, length of filaments and length of ovary are found to be highly significant. High coefficient of variation is recorded for hermaphrodite (183.84) and pistillate (171.71%) flowers. The pollen viability of the hermaphrodite flowers are found less as compared to the staminate flowers. The percentage of pollen viability is 79.74% and 90.77% in hermaphrodite and male flower respectively. In the population studied, the occurrence of hermaphrodite flower in monoecious tree ranged from 0 - 10%.